Implikasi Hukum Internasional dan Nasional dalam Kasus Transfer Minyak Ilegal oleh Kapal Tanker MT Horse dan MT Freya di Perairan Indonesia - Sirait, Naomi Margaretha Ghokmaria (Media Hukum Indonesia (MHI), 2025)
incident involving the tanker vessels MT Horse and MT Freya is a violation of the right to innocent passage in Indonesia. Indonesia itself is the first and only country that has established Archipelagic Sea Lanes within its archipelagic waters, also known as the Indonesian Archipelagic Sea Lanes (ALKI). The establishment of these sea lanes grants Indonesia specific obligations and authority to enforce laws and regulations that correspond with the application of archipelagic sea lanes as stated by UNCLOS 1982 aimed at facilitating the continuity of foreign ship passage while at the same time protecting the security, safety, and sovereignty of the nation within its waters. In this case, both tankers violated the right of innocent passage and the right of transit passage established by the 1982 United Nations Convention on the Law of the Sea (UNCLOS), as well as Indonesian state laws governing navigation, customs, and marine environmental protection. According to the research findings, the illegal transfer of oil from ship to ship while anchored, unauthorized loading and unloading activities, and disabling of the Automatic Identification System (AIS) by both vessels violate not only UNCLOS 1982 provisions but also national regulations such as Law No. 17 of 2008 on Shipping and Law No. 32 of 2009 on Environmental Protection and Management. Indonesian authorities enforced the law by arresting and prosecuting the culprits, resulting in criminal charges and penalties. This study demonstrates the necessity of international and national law cooperation in preserving sovereignty, maritime security, and protecting Indonesia's marine environment.